2018
DOI: 10.3389/fmicb.2018.01032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Capacity of Human Gut Microorganisms to Colonize the Zebrafish Larvae (Danio rerio)

Abstract: In this study we evaluated if zebrafish larvae can be colonized by human gut microorganisms. We tested two strategies: (1) through transplantation of a human fecal microbiota and (2) by successively transplanting aerotolerant anaerobic microorganisms, similar to the colonization in the human intestine during early life. We used conventionally raised zebrafish larvae harboring their own aerobic microbiota to improve the colonization of anaerobic microorganisms. The results showed with the fecal transplant, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Microbial consortia, strains, or their products can be added to the housing media to test their impact on host biology or their ecology in association with the host. Inoculation of GF zebrafish larvae with complex bacterial communities or defined strains demonstrated that even some mammalian commensal taxa, such as Escherichia, Enterococcus, Bacillus, Roseburia , and Prevotella , can colonize zebrafish larvae (22, 42), thus enabling the use of “humanized” zebrafish to for medium-throughput investigation of host-microbiota interactions. Furthermore, probiotic bacterial strains including several species of Lactobacilli , colonize zebrafish and can influence host immune responses and outcomes to bacterial infection (3739, 43, 44).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial consortia, strains, or their products can be added to the housing media to test their impact on host biology or their ecology in association with the host. Inoculation of GF zebrafish larvae with complex bacterial communities or defined strains demonstrated that even some mammalian commensal taxa, such as Escherichia, Enterococcus, Bacillus, Roseburia , and Prevotella , can colonize zebrafish larvae (22, 42), thus enabling the use of “humanized” zebrafish to for medium-throughput investigation of host-microbiota interactions. Furthermore, probiotic bacterial strains including several species of Lactobacilli , colonize zebrafish and can influence host immune responses and outcomes to bacterial infection (3739, 43, 44).…”
Section: Introductionmentioning
confidence: 99%
“…Valenzuela et al, 2018). The successful colonisation of the larval gut with anaerobic species, including Lactobacillus paracasei and strict anaerobes such as Eubacterium limosum and…”
mentioning
confidence: 99%
“…The gut microbiota of human and zebrafish are different. Valenzuela et al (2018) showed that germ-free zebrafish larvae can be colonized by human gut microorganisms, such as Clostridioides difficile and Bacillus. This result opened an interesting area to study interactions between these microorganisms and the host.…”
Section: Zebrafish As a Model For The Study Of Intestinal Diseases Anmentioning
confidence: 99%